Website Quality Analysis of the Ogan Ilir District Health Office Using the WebQual Method - Muhammad Fikri Upersa (Institute of Information Technology and Social Science (IITSS), 2023)
Information technology is one of the most widely utilized and continually improved tools in both private and public institutions. The Ogan Ilir District Health Office has adopted this technology through its official website, which functions as an information platform to communicate organizational performance, publish health-related data, and serve as an information resource for users. However, several weaknesses remain, including the absence of login or registration features (which prevents user interaction), the lack of a search function, outdated gallery content, and a non-responsive, less appealing interface. This study aims to analyze the quality of the Ogan Ilir District Health Office website using the WebQual 4.0 method, which evaluates usability, information quality, and service interaction quality based on user perceptions. The study adopts a quantitative approach to identify the extent to which these dimensions influence user satisfaction.